Exploring negotiations of space and safety by international African students in South African higher education - Hoxobes, Gezina (My University, 2019)
This study employed a phenomenological analysis to explore the negotiations of space and safety by international African students in South African higher education. Issues of how international African students enhance their safety, what identity consequences these safety enhancements have and how the sense of community amongst international African students influences their psychological wellbeing were of pertinence to this study. This study included international African students from the University of the Witwatersrand and the University of Pretoria, totalling 13 participants. It was found that international African students: employ diverse mechanisms to enhance their safety; have inhibitions to self-expression and enablers to identity expression in enhancing their safety; have a poor sense of community; experience feelings of happiness, sadness and loneliness as well as indifference and; have encountered xenophobia in diverse forms. These findings contribute to the scant body of knowledge about the experiences of international African students within the South African context and so encourages further research in this area.
A dissertation submitted to the School of Human and Community Development in partial fulfillment of the requirements for the degree of Masters in Community-Based Counselling Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2019
Keywords: Ethnicity; Xenophobia; Racism; Race relations